Hijab in the Qur'an and the Contemporary Context (Double Movement Theory Analysis) - Islamy, Nur Izzah; Rahman Akbar, Ahmad Fadly (Transformatif, 2024)
This paper discusses Muslim women's clothing, namely the issue of hijab. The term hijab in the Qur'an is also related to the terms khimar and jilbab. There are pros and cons related to the obligation to wear the hijab, as happened in Iran and Aceh. Because of the compulsion to wear the hijab, Iranian women are struggling to regain control over their own bodies, because this concerns women's right to choose how to dress. Thus, this article aims to examine how the hijab and related issues in the Qur'an are based on the socio-historical context with the Double Movement theory analysis approach. Therefore, this article is expected to find the universal value of the verse of hijab command in the Qur'an in the context of today.